Bioprocessing Technology in Food and Health: Potential Applications and Emerging Scope - Verma, Deepak Kumar; Patel, Ami R.; Srivastav, Prem Prakash; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
The functional foods market represents one of the fastest growing and most fascinating areas of investigation and innovation in the food sector. This new volume focuses on recent findings, new research trends, and emerging technologies in bioprocessing: making use of microorganisms in the production of food with health and nutritional benefits. The volume is divided into three main parts. PartI discusses functional food production and human health, looking at some newly emerged bioprocessing technological advances in the functional foods (chocolates, whey beverages) in conjunction their prospective health benefits. Part II, on emerging applications of microorganism in safe food production, covers recent breakthroughs in food safety in microbial bioprocessing. Chapters discuss spoilage issues, harmful/pathogenic microorganisms, genetically modified microorganisms, stability and functionality, and potential of food-grade microbes for biodegradation of toxic compounds, such asmycotoxins, pesticides, and polycyclic hydrocarbons. Chapters in Part III, on emerging scope and potential application in the dairy and food industry, explore and investigate the current shortcomings and challenges of the microbially mediated processes at the industrial level. The editors have brought together a group of outstanding international contributors at the forefront of bioprocessing technology to produce a valuable resource for researchers, faculty, students, food nutrition and health practitioners, and all those working in the dairy, food, and nutraceutical industries, especially in the development of functional foods.
Importance of Chocolates in Functional Foods: Formulation, Production Process, and Potential Health Benefits -- --Nevzat Konar, Omer Said Toker, Ibrahim Palabiyik, Derya Genc Polat, Sirin Oba, and Osman Sagdic -- Fermented Whey Beverages: As Functional Foods and Their Health Effects -- --Tatiana Colombo Pimentel, Michele Rosset, Suellen Jensen Klososki, Carlos Eduardo Baro, and Adriano Gomes da Cruz -- Genetically Modified Organisms (GMOs) Produced Enzymes: Multifarious Applications in Food Manufacturing Industries -- --Deepak Kumar Verma, Kimmy G., Pratibha Singhal, Rishika Vij, Dipendra Kumar Mahato, Ami Patel, and Prem Prakash Srivastav -- Potential Role of Food Microbial Communities (FMCs) in Different Food Production and Human Health -- --Deepak Kumar Verma, Kimmy G., Alaa Kareem Niamah, Ami Patel, Rishika Vij, and Prem Prakash Srivastav -- Production of Extracellular Polymeric Substances (EPS) from Lactic Acid Bacteria (LAB): Their Antimicrobial Effect and Potential Application in the Food Industry -- --Goksen Gulgor and Mihriban Korukluoglu -- Utilization of Bacteriophages Targeting Listeria monocytogenes in the Dairy and Food Industry -- --Andrei Sorin Bolocan, Luminia Ciolacu, Elena-Alexandra Oniciuc, Lorraine Draper, Anca Ioana Nicolau, Martin Wagner, and Colin Hill -- Significance of Food Grade Microorganisms in Biodegradation and Biotransformation of Harmful Toxic Compounds -- --Ami Patel, Pooja Thakkar, Nihir Shah, Deepak Kumar Verma, and Prem Prakash Srivastav -- Tailoring the Functional Benefits of Whey Proteins by Encapsulation: A Bottom-Up Approach -- --Nicoleta Stnciuc, Gabriela Rpeanu, and Iuliana Aprodu
Includes bibliographical references and index.
Also available in print format.
Keywords: Functional foods; Food -- Microbiology; Food industry and trade -- Technological innovations; Food Microbiology; Functional Food -- microbiology; Fermented Foods -- microbiology; Food-Processing Industry; Electronic books